2010
DOI: 10.3758/brm.42.3.768
|View full text |Cite
|
Sign up to set email alerts
|

O-Cam: A new paradigm for investigating the effects of ostracism

Abstract: A new ostracism paradigm-O-Cam-was designed to combine the best qualities of both social ostracism (i.e., face-to-face interaction between the target and sources of ostracism) and cyber ostracism (i.e., confederatefree, highly controlled designs) paradigms. O-Cam consists of a simulated Web conference during which participants are either ostracized or included by 2 other participants whose actions, unbeknownst to the participants, are actually pretaped. The findings of preliminary studies indicate that O-Cam p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Not including a task with high likelihood of eliciting SCE may have limited our ability to examine the relevance of SCE-related temporal dynamics as effectively as possible. Although our use of several different emotion induction tasks with the potential to elicit a wide range of emotions was a strength, future research can improve upon the present study by including tasks that target SCE and its triggers (e.g., social rejection, ethical indiscretions) more directly, such as the O-Cam task (Goodacre & Zadro, 2010) or individualized emotional scripts (see Kuo, Neacsiu, Fitzpatrick, & MacDonald, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Not including a task with high likelihood of eliciting SCE may have limited our ability to examine the relevance of SCE-related temporal dynamics as effectively as possible. Although our use of several different emotion induction tasks with the potential to elicit a wide range of emotions was a strength, future research can improve upon the present study by including tasks that target SCE and its triggers (e.g., social rejection, ethical indiscretions) more directly, such as the O-Cam task (Goodacre & Zadro, 2010) or individualized emotional scripts (see Kuo, Neacsiu, Fitzpatrick, & MacDonald, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Cyberball is only a simulation of rejection and does not reflect all aspects of social rejection in the real world. Further studies could use more complex simulations, like the “O-Cam” technique reported in (Goodacre and Zadro, 2010). Further, anecdotal reports of MDMA’s effects on social feelings and behavior generally come from settings in which the drug is taken with others, while in this and all other laboratory studies so far, participants have taken the drug alone.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, being excluded by real people is not always necessary to induce feelings of exclusion as it has been shown that exclusion by a computer is also sufficient to induce feelings of exclusion (Zadro et al, 2004). A recent alternative paradigm that future studies could use is the new paradigm “O'cam,” which is more ecologically valid than the Cyberball game as it contains a Web-based interaction between the participant and (pre-recorded) excluders (Goodacre & Zadro, 2010). Because relational bullying is likely to be an ongoing and repetitive process (Olweus, 1991; Roland, 1989), the manipulation of social exclusion could also be varied in intensity and over time.…”
Section: Discussionmentioning
confidence: 99%